Tinjauan Yuridis Penerapan Prinsip Hukum Waris dalam Sengketa Kepemilikan Berbasis Hukum Waris Adat Tionghoa ditinjau dari Hukum Positif di Indonesia - Jeanice Chrisadi; Bambang Daru Nugroho; Yani Pujiwati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The pluralistic development of Indonesian national law creates a dynamic relationship between national civil law and customary law, including in the context of resolving inheritance disputes in Chinese families who adhere to patrilineal traditions. Supreme Court Decision No. 1204 K/Pdt/2024 shows that there is a tension between legal certainty under the Civil Code and substantive justice originating from living law. This research aims to analyze the judge's interpretation of family documents as a basis for inheritance rejection, inheritance sharing mechanisms that ignore Chinese customary norms, and their implications for legal pluralism in Indonesia. The method used is normative juridical with a case study approach and a descriptive-analytical legislative approach, using literature studies of primary, secondary and tertiary legal materials. The results showed that the ruling applied neither the Civil Code nor the principle of Chinese customary inheritance consistently. The family declaration on which the judge relied was not actually a refusal of inheritance, but an internal agreement granting authority to the testator. Moreover, the distribution of inheritance carried out is not in accordance with the principle of patrilineal custom which places the eldest son as the recipient of the largest share. This finding shows the weak application of legal pluralism (weak legal pluralism) and reveals the gap between das sollen and das sein, so it is necessary to strengthen the role of judges in exploring the traditional values that live in society.